Influence of sand/cement ratio on mechanical properties of palm kernel shell concrete - Mahmud, Hilmi; Jumaat, Mohd Zamin; Alengaram, U.J. (Journal of Applied Sciences, 2009)
An experimental investigation was carried out to improve the mechanical properties of Palm Kernel Shell Concrete (PKSC) by varying sand content and incorporating mineral admixtures, to achieve strength of 35 MPa. The mineral admixtures included 10 silica fume as additional cementitious material and 5 class F fly ash as cement replacement material. Sand to cement ratio (s/c) was varied between 1.0 and 1.6 and superplasticizer was added to all mixes to provide adequate workability. Twenty-eight days saturated density and compressive strength of the concrete were in the range of 1850-1960 kg m-3 and 28-38 MPa. respectively. Increase in sand content has positive influence on the mechanical properties of concrete. When the sand to cement ratio was increased from 1.0 to 1.6. increase in 28 day compressive strength by about 24 was noted for a small density increase of about 4. The other mechanical properties such as flcxural and splitting tensile strengths were found in the range of 2.76-4.76 and 1.9-2.61 MPa. respectively over a period of 90 day. The static modulus of elasticity was in the range of 8-11 GPa. These results confirm that the combined use of maximum sand to cement ratio of 1.6 and mineral admixtures have significant influence on the mechanical properties as compared to the previous research findings. The addition of silica fume resulted in cohesive mix and use of a superplasticizer can provide slump in the range of 65-105 mm. However, an increase of s/c ratio beyond 1.6 is likely to increase the concrete density above 2000 kg m-3.